2017
DOI: 10.1007/s12070-017-1237-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracorporeal Septoplasty in Severely Deviated Nasal Septum

Abstract: Extracorporeal septoplasty is a valuable tool in the armamentarium of the nasal surgeon for the reconstruction of the severely deviated septum. Extracorporeal septoplasty offers the surgeon the opportunity to correct the septum under direct visualization, shape the nasal vault and address the nasal dorsum with the ultimate goal of providing both form and function for the patient with a complex septal deviation. The study was conducted with the aim to measure the outcomes of extracorporeal septoplasty in severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This study demonstrated that ESR could significantly improve postoperative nasal patency. About the evaluation of the aesthetic outcomes in ESR technique, Baser et al 20 described the postoperative aesthetic outcomes in ESR technique with 35 patients. This study reported that 32 (91.43%) patients showed significant improvement of aesthetic satisfaction and only 3 (8.5%) patients showed there is no improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrated that ESR could significantly improve postoperative nasal patency. About the evaluation of the aesthetic outcomes in ESR technique, Baser et al 20 described the postoperative aesthetic outcomes in ESR technique with 35 patients. This study reported that 32 (91.43%) patients showed significant improvement of aesthetic satisfaction and only 3 (8.5%) patients showed there is no improvement.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that ESR could significantly improve postoperative nasal patency. About the evaluation of the aesthetic outcomes in ESR technique, Baser et al 20 Because of the limitation of ES technique, the outcomes of the nasal obstruction were significantly less improved and it was not effective in improving the nasal aesthetic satisfaction. About the surgical complications, Dąbrowska-Bien ét al 24 conducted a study about the complications of nasal septoplasty in a large group of 5639 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many of these changes occur gradually over a period of years, middle vault anatomy has been increasingly emphasized in an effort to reduce these factors that lead to nasal valve compli-cations. 3,4 While dorsal preservation rhinoplasty is not the focus of this article, recent increased interest in these techniques is, in part, due to the avoidance of a need for middle vault reconstruction. By preserving the dorsal anatomy in lieu of traditional dorsal hump excisional techniques, dorsal preservation rhinoplasty avoids many of the functional and cosmetic middle vault issues seen with other approaches.…”
Section: Significance Of the Middle Vaultmentioning
confidence: 99%
“…13 Suture techniques to fix the caudal portion of the neoseptum to avoid narrowing of the internal nasal valve is vital. 3 Classic extracorporeal septoplasty has a significant rate of postoperative dorsal irregularity and, occasionally, saddle-nose deformity. A modification of the extracorporeal septoplasty technique to minimize these complications is anterior septal reconstruction or transplantation, where the majority of the dorsal strut is left intact and the caudal strut is replaced.…”
Section: Management Of the Septummentioning
confidence: 99%